If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24n + -10n + 36 = 0 Reorder the terms: 36 + 24n + -10n = 0 Combine like terms: 24n + -10n = 14n 36 + 14n = 0 Solving 36 + 14n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-36' to each side of the equation. 36 + -36 + 14n = 0 + -36 Combine like terms: 36 + -36 = 0 0 + 14n = 0 + -36 14n = 0 + -36 Combine like terms: 0 + -36 = -36 14n = -36 Divide each side by '14'. n = -2.571428571 Simplifying n = -2.571428571
| 10z-z=3+3z-3-12 | | 47g^2+50g=0 | | 7[x+(-11)]+(-3)=-53 | | X*11=35 | | 6x-108/5=2x | | -31+8x=29+6x | | y=29-4(6) | | 4sin^2x+2=5 | | y=29-4(5) | | X(3x+2)=23 | | y=29-4(4) | | 4/5=x-3/9 | | 7[x+(11)]+(-3)=-53 | | 2/5(d-3)=30 | | y=29-4(1) | | 6x-30=x-25 | | 9g-15=21 | | 3.4x=1.8x+2.5 | | 5x-6+2x=9x-7 | | 9j^2+42j+49=0 | | 3x^2+15x-9.1=0 | | h=3(1)+1 | | 0.2c+0.08c-3.6c=0 | | 9=9-11x | | 0.3(y+2)=24 | | 10z^2-1440=0 | | 28-2u=5u | | 2x+14=-5x-11 | | -5/4m-1/6=7/3 | | 4x-2=7-2x | | 8+3x-9x=20 | | 0=1-x+y |